Knockdown of RAD51AP1 suppressed cell proliferation and invasion in esophageal squamous cell carcinoma - Yang-Yang Hu; Chen-Chao Ma; Kai-Xing Ai (Discover Oncology, 2022)
Abstract Background Esophageal cancer is a common malignant tumor of digestive tract with esophageal squamous cell carcinoma (ESCC) being the main histological subtype. This study aimed to identify potential hub gene associated with the pathophysiology of ESCC through bioinformatics analysis and experiment validation. Methods Three microarray datasets were obtained from the Gene Expression Omnibus (GEO) database. The overlapping differentially expressed genes (DEGs) were analyzed by GEO2R tool. Gene Ontology (GO) and Kyoto Encyclopedia of Genes (KEGG) pathway analyses were performed to predict the potential functions of DEGs. Nine hub genes were identified using protein–protein interaction (PPI) network and Cytoscape software. We selected RAD51-associated protein 1 (RAD51AP1) for further research because of its poor prognosis and it has not been sufficiently studied in ESCC. The effects of RAD51AP1 on proliferation, apoptosis, migration and invasion of ESCC cells were determined by in vitro functional assays. Results RAD51AP1 expression was significantly upregulated in ESCC tissues compared with normal tissues by using The Cancer Genome Atlas (TCGA) database. High expression of RAD51AP1 was associated with worse survival in ESCC patients. RAD51AP1 expression was positively associated with the enrichment of Th2 cells and T helper cells. Furthermore, CCK-8 and colony formation assays showed knockdown of RAD51AP1 inhibited the proliferation of ESCC cells. Flow cytometry analysis indicated knockdown of RAD51AP1 induced cell cycle arrest and apoptosis in ESCC cells. Transwell assay revealed knockdown of RAD51AP1 suppressed the migration and invasion of ESCC cells. Conclusions Finally, our results demonstrated that RAD51AP1 silencing significantly inhibited cell proliferation and invasion in ESCC, thereby highlighting its potential as a novel target for ESCC treatment.